FOREIGN LANGUAGE VOCABULARY AS A CREATIVE BASE OF MODERN NICKNAMES OF WESTERN POLISSYA RESIDENTS - Шульська, Наталія (Current Issues of Foreign Philology, 2021)
The article provides a comprehensive analysis of generic lexemes of the nicknames of residents of Western Polissya that reflect foreign-language realities and demonstrate the use of interlingual borrowings. Collected anthroponymic facts about the lexical creation base and isolated informal names with foreign-language components are differentiated. All nicknames with formation-borrowings, which are included in the research arsenal, are divided into lexical-thematic groups. Each anthroponym is analysed from the sight of motivational characteristics. It was found that nicknames are the main anthroponymic category in consumer communication and in social micro-communities. In Western Polissya the use of dialect variants of the term nickname is predominantly following: street name, street nickname, menu, fiction, calligraphy, fake, nickname / clique. The unofficial nominations that originated from borrowed names, foreign language appeals, names of foreign politicians, historians, actors, athletes, public figures, heroes of advertisements, movie and multiheroes are analysed in detail. It was found out that street names, created from foreign language realities, are mostly modern nicknames, which appeared relatively recently. Such unofficial names appear mainly in students' or work collectives; creators and carriers of these nicknames are young people. The largest amount of borrowings was found from Russian and Polish, due to constant interlingual contacts and historical conditions. Among the creation base of the individual Western-nicknames created by external and internal peculiarities, as well as by the occupation, interferential lexemes from the English language have become productive. Sporadically, in the unofficial noun Polishuk, borrowings from French, German, Spanish, Belarussian, Hebrew, and other languages were fixed.